The prognostic value of perfusion MRI in cerebral glioma - Manita, Muftah (2012)
Introduction Cerebral glioma is the most prevalent primary brain tumour, of which the majority are high grade gliomas. High grade gliomas possess a poor prognosis, and glioblastoma patients survive less than one year after diagnosis. To date, histological grading is used as the standard technique for diagnosis and survival prediction. Previous studies using advanced techniques such as MR Perfusion have achieved a high sensitivity but a low specificity in identifying high grade gliomas. Moreover, they have failed to distinguish glioblastoma from anaplastic glioma. The purpose of the study presented here is to assess the diagnostic and prognostic value for cerebral glioma of cerebral blood volume maps derived from MR perfusion.